The role of contrast-enhanced and non-contrast-enhanced MRI in the follow-up of multiple sclerosis. (July 2021) - Zarei, Fariba; Ghaedian, Mehrnaz; Ghaedian, Tahereh
Background: Magnetic resonance imaging (MRI) is widely used in patients with multiple sclerosis (MS) for different indications. However, frequent administration of gadolinium in these patients can have some potential complications. So, a more limited approach reducing the use of gadolinium should be considered. Purpose: To evaluate the additional benefits of contrast-enhanced MRI over non-contrast-enhanced MRI in routine follow-up of patients with MS. Material and Methods: This is a retrospective cohort study including patients with MS who underwent both contrast-enhanced and non-contrast-enhanced MRI for two time-points with an interval of at least six months. Non-contrast-enhanced images were compared for each patient and interpreted as non-progressive or progressive disease. Then, rate and type of enhancing lesions were analyzed and compared between the groups. All images were reviewed and compared visually by two radiologists. Results: A total of 462 patients (392 women; mean age = 36 years) were included. Of these patients, 352 were in the non-progressive group and 112 were in progressive group. Comparison of baseline and follow-up contrast-enhanced MRIs revealed that 13 (3.7%) patients in the non-progressive group and 58 (51.8%) patients in progressive group developed enhancing lesions ( P  < 0.001). All 58 patients in the progressive group developed new enhancing lesions, whereas all those in the non-progressive group revealed persistent or reactivated enhancing lesions without evidence of new lesions. Conclusion: According to the very low incidence rate of new enhancing lesions in patients with non-progressive disease on follow-up non-contrast-enhanced MRI, routine administration of contrast in follow-up studies is not suggested.